2014
DOI: 10.9790/0853-131232328
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Epidural, Bupivacaine with Buprenorphine and Bupivacaine with Fentanyl in Lower Limb Surgeries

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Its highly lipophilic property allows it to be rapidly absorbed into the spinal venous plexus and thus carries lesser risk of respiratory depression associated with rostral (10) spread of the drug. Santhosh Kumar et al, in a study comparing fentanyl and buprenorphine when given as an adjunct with bupivacaine found no difference in time taken to achieve motor (11) blockade. A similar study by Chakravarthy N N et al, comparing Nalbuphine and Fentanyl found signicantly longer duration of sensory blockade in the Nalbuphine group thus a prolonged duration of (12) analgesia in the Nalbuphine group.…”
Section: Discussionmentioning
confidence: 99%
“…Its highly lipophilic property allows it to be rapidly absorbed into the spinal venous plexus and thus carries lesser risk of respiratory depression associated with rostral (10) spread of the drug. Santhosh Kumar et al, in a study comparing fentanyl and buprenorphine when given as an adjunct with bupivacaine found no difference in time taken to achieve motor (11) blockade. A similar study by Chakravarthy N N et al, comparing Nalbuphine and Fentanyl found signicantly longer duration of sensory blockade in the Nalbuphine group thus a prolonged duration of (12) analgesia in the Nalbuphine group.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Kumar and Kaladhar demonstrated that the onset of analgesia was faster in the butorphanol group than in the buprenorphine group; however, analgesia duration was longer in the buprenorphine group (17). Various studies have demonstrated that buprenorphine is effective as an analgesic for postoperative pain (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%